2016
DOI: 10.1111/jav.01000
|View full text |Cite
|
Sign up to set email alerts
|

Trade‐offs between reproduction and self‐maintenance (immune function and body mass) in a small seabird, the little auk

Abstract: Breeding season is the most energetically and physiologically demanding phase in the avian annual cycle, challenging adults' physiology and survival. However, the timing and extent that self‐maintenance of breeding adults is compromised during the breeding season is poorly understood. We investigated the trade‐off between reproduction and self‐maintenance in relation to breeding phase (prelaying, incubation, chick rearing) and sex in a small Arctic seabird, the little auk Alle alle. To measure a bird's allocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…We suggest that those differences may be attributed to breeding stage dependent changes in hormone levels, that in turn, affect various haematological parameters, including the oxidative status. Lack of sex differences in the oxidative status, along with some other studies (Wojczulanis- , 2014, Kulaszewicz et al 2017, further undermines hypothesis about the little auk female ceasing the chick provisioning earlier than male due to her worse body condition. Nevertheless, since our study is correlational with a cross-sectional design, to fully comprehend seasonal changes in OS and hormones as well as causality of the observed patterns, further, preferably experimental studies are needed, possibly also including earlier breeding stages.…”
Section: Discussionmentioning
confidence: 94%
“…We suggest that those differences may be attributed to breeding stage dependent changes in hormone levels, that in turn, affect various haematological parameters, including the oxidative status. Lack of sex differences in the oxidative status, along with some other studies (Wojczulanis- , 2014, Kulaszewicz et al 2017, further undermines hypothesis about the little auk female ceasing the chick provisioning earlier than male due to her worse body condition. Nevertheless, since our study is correlational with a cross-sectional design, to fully comprehend seasonal changes in OS and hormones as well as causality of the observed patterns, further, preferably experimental studies are needed, possibly also including earlier breeding stages.…”
Section: Discussionmentioning
confidence: 94%
“…Both common and Brünnich's guillemots reduce body mass following incubation at the onset of chick rearing (Birkhead and Nettleship 1987, Harris and Wanless 1988, Croll et al 1991, Gaston and Perin 1993, Elliott et al 2008b), which is observed in other seabird species too (Niizuma et al 2001, Schultner et al 2013, Kulaszewicz et al 2016). In guillemots, this reduction in adult body mass post‐hatching can be quite rapid, resulting in ca 5–10% body mass loss over just a few days (Gaston and Perin 1993).…”
Section: Discussionmentioning
confidence: 95%
“…Meanwhile, a study of Little Auks Alle alle found that the adults themselves suffered a cost of reproduction to their immune function instead of the chicks (Kulaszewicz et al . 2017), a strategy more commonly expected in short‐lived species (Tinbergen & Williams 2002). Saino et al .…”
Section: Discussionmentioning
confidence: 99%